Normative influence in a time of distrust and polarization: how perceived social norms predict COVID-19 vaccination intentions among Black Americans. - Lin, Tong; Wang, Yuan; Thier, Kathryn; Nan, Xiaoli (Journal of Behavioral Medicine, 2025)
This study examined the impact of social norms—descriptive, injunctive, and subjective norms—on COVID-19 vaccination intentions among Black Americans. It also investigated how Black Americans affiliated with Democrats and Republicans perceived norms within their groups and how such perceptions influenced their COVID-19 vaccination intentions. We conducted an online national survey with Black Americans (N = 1497) between February and March 2021. Results showed that all three types of norms were significantly and positively associated with vaccination intentions, with subjective norms exerting the strongest effect. Additionally, higher subjective norms amplified the positive relationship between descriptive norms and vaccination intentions. Republicans were influenced by both in-group and out-group norms, while Democrats were primarily guided by in-group norms, underscoring the potential of bipartisan messaging to boost vaccine uptake. These findings highlight how social norms impact COVID-19 vaccination intentions and reveal that individuals with differing party affiliations are influenced differently based on their perceived identification with reference groups. The study provides insights for designing targeted interventions to improve vaccine uptake among Black Americans and for developing broader public health messaging strategies. It contributes to the literature by revealing how the interplay of descriptive, injunctive, and subjective norms shapes vaccination intentions and by offering a novel perspective on the differentiated effects of in-group and out-group norms based on partisan identity.